Permodelan Pertumbuhan dan Produksi Kelapa Sawit pada Berbagai Taraf Penunasan Pelepah - Gromikora, Nope; Yahya, Sudirman; ,, suwarto (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2014)
ABSTRACTThe numbers of leaf frond influence oil palm yield, especially fresh fruit bunch weight and fresh fruit bunch production. The objective of this research was to obtain oil palm growth and production model for different levels of frond pruning. The experiment was conducted at PT. Astra Agro Lestari, Pangkalan Bun, Central Kalimantan, from August 2010 to February 2012. The experiment was arranged in a randomized block design with two factors and three replications for each oil palm age. The first factor was numbers of unpruned frond and the second factors was pruning seasons. The frond treatment consisted of 41-48, 49-56, and 57-64 fronds. The pruning seasons consisted of first period (early to mid rainy season: September-December), second period (mid to end of rainy season: Januari-April), and third period (dry season: May-August). Stella production model was created based on pruning experiment and weather data. The constructed production model was able to estimate 75% variable of oil palm production and fresh fruit bunch weight at different levels of pruning. Keywords: oil palm, pruning management, Stella model